INNOVATIVE DEVELOPMENT OF LEGAL SCIENCE - Сопілко, Ірина Миколаївна; Череватюк, Вікторія Богданівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Objective: summarizing the results of the X International Scientific and Practical Conference «Innovative Development of Legal Science in the Conditions of Modernization of Society» and clarifying the role of science i the innovative development of the state. Methods: general and special scientific (special) methods were used to achieve this goal, in particular the method of functionally legal, structural - systemic, generalization and others. The use of these methods made it possible to outline the problems of the formation and development of modern legal science and the prospects for its innovative development. Results: the participants of the conference outlined the tasks that are on the agenda of Ukrainian legal science in the context of society’s modernization, in particular, the strengthening of innovative directions of scientific research, the creation of new scientific paradigms, the formation of a stable methodological basis that will allow to achieve the state of scientific maturity of legal science in Ukraine, as a system of knowledge and ways and means of constructing legal reality. It is stated that the formulated approaches to the understanding of judicial jurisdiction make it difficult to protect the infringed law for specific entities requiring such protection, which indicates the need to distinguish categories of disputes which are considered in administrative proceedings from those considered in civil proceedings. Discussion: the innovative development of the state is not possible without a scientific background; the issues of training legal scholars and their integration into the world scientific space remain debatable. During the discussion, legal scholars representing various fields of law shared their achievements in their respective fields of activity. It also deserves attention on important issues related to the fact that there is a more important change in the concept of innovation, and the need for practical implementation of change should be highlighted, namely, to emphasize the nature and purpose of such change. Innovation, in this case, is the introduction into practice, implementation and use of innovation (ideas, proposals, research solutions, models). During the conference, a number of innovative proposals was presented, in particular, proposed in the field of aerospace cyberspace: to develop and adopt at the legislative level the concept of aerospace security in cyberspace; create an interstate legal program for the use of outer space in educational, scientific and praxeological activities; to develop a legal system for preventing and counteracting the harmful use of outer space at both national and interstate (world) levels. According to the results of the conference, the scientists have identified for themselves the prospects of innovative scientific research, in particular, grid and blockchain for the prevention of aerospace cybercrime; study of the concept and legal bases of aerospace cyber security.